Influence of Didactic Use and Attitude toward Educational Apps for Mobile Learning (Docentes 2.0 Journal, 2024)
In today's digital era, mobile devices have become an integral part of our lives, giving us instant access to various applications and services. The research aims to determine the influence of didactic use and attitude toward educational apps for mobile learning in high school students. The research was based on the positivist paradigm, deductive method, quantitative approach, non-experimental design, correlational type, and cross-sectional. The selected sample consisted of 262 students from middle school institutions in the central province of the Boyacá department. Questionnaires were designed for data collection: didactic use, the scale of attitude towards Apps, and mobile learning. The reliability was calculated with Cronbach's alpha technique, which was 0.81, 0.90, and 0.71, respectively. The inferential calculation showed a significant positive correlation with an intermediate level between didactic use of educational Apps and attitudes towards Apps for mobile learning. Therefore, it was evidenced that the didactic use of educational Apps and attitudes towards them were positive, moderately significant predictors of mobile learning. The results showed that 50% of the students present a medium-low level of use of educational apps. Likewise, 54% perceive a medium-low attitude. It was concluded that it is necessary to promote mobile learning policies in educational institutions to learn about the educational potential offered by emerging technologies.
Keywords: Didactic use; attitude; educational applications; mobile learning; students